Effects of postbiotic products from Saccharomyces cerevisiae fermentation on lactation performance, antioxidant capacity, and blood immunity in transition dairy cows - Dongwen Dai; Fanlin Kong; Haoqi Han; Weina Shi; Han Song; Ilkyu Yoon; Shuo Wang; Xiaojing Liu; Na Lu; Wei Wang; Shengli Li (Journal of Dairy Science)
ABSTRACT: This study aimed to evaluate the effects of dietary supplementation with different types of Saccharomyces cerevisiae fermentation products (SCFP) on lactational performance, metabolism, acute phase protein response, and antioxidant capacity in dairy cows from −21 to 56 DIM. A total of 180 multiparous Holstein dairy cows were blocked by parity, expected calving date, pre-trial BCS, and previous 305-d mature-equivalent milk yield, and then randomly assigned to 1 of 3 dietary treatments: the basal control diet (CON; n = 60), the basal diet supplemented with 40 g/d of XPC (XPC; n = 60; Diamond V, Cedar Rapids, IA), and the basal diet supplemented with 19 g/d of NutriTek (NTK; n = 60, Diamond V). Blood (n = 15, 13, and 12 in the CON, XPC, and NTK groups, respectively) was sampled at −7 (± 3), +3, +7, +21, and +28 d, and milk (n = 19, 18, and 15 in the CON, XPC, and NTK groups, respectively) was sampled from 1 to 8 wk from a subset of cows from −21 to 56 d relative to calving. Data were analyzed using the MIXED procedure in SAS (SAS Institute Inc.). All data were subjected to repeated measures ANOVA. Dietary treatment (Trt), time, and their interaction (Trt × time) were considered as fixed effects and cow as the random effect. Cows fed XPC and NTK had greater ECM yield. Supplementing NTK increased milk fat content and yield and 3.5% FCM yield compared with CON. Milk urea nitrogen was lower in XPC cows than CON. We found that SCFP supplementation decreased plasma BHB, ceruloplasmin, haptoglobin (HPT), and IL-1β concentrations, and it increased plasma P concentrations. In addition, cows fed NTK showed lower creatinine (CR) and cortisol concentrations but increased plasma Ca and myeloperoxidase concentrations than CON cows. In addition, cows fed NTK and XPC both had reduced plasma concentrations of serum amyloid-A (SAA) at 3 DIM compared with CON cows. Furthermore, SCFP cows had greater concentrations of plasma glucose and Ca than CON cows at 7 DIM, and greater concentrations of plasma P at 21 DIM. Between the groups fed different types of SCFP, plasma concentrations of nonesterified fatty acids, malondialdehyde, CR, SAA, and HPT were lower in cows fed NTK compared with cows fed XPC at 7 DIM. Overall, our results indicate the potential benefits of supplementing SCFP in transition dairy cows by modulating immunity and liver metabolic function and supporting ECM yield. The results also suggest that NutriTek at 19 g/d appears to support the performance and health of dairy cows better compared with XPC at 40 g/d, based on improved metabolic and inflammatory status during the transition period.